Barang Siapa Di Antara Kamu Tidak Berdosa, Hendaklah Ia Yang Pertama Melemparkan Batu Kepada Perempuan Itu - Yerni Ndruru (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2016)
All humans are sinful and no one is without sin. The intended sinfulness applies to everyone, no matter what their religious status or whatever their social status. Through this incident in John 8, from the words Jesus gave about 'whoever is without sin' it is very clear that all men have sinned so that no one is without sin. Sin deserves to be punished. But in this case, the sins committed by adulterous women were not punished by Jesus. This does not mean that Jesus was abolishing the law, but Jesus made it clear that the sinfulness of mankind must be redeemed and that redemption was not enough with the sacrifice made every year according to the law. Permanent redemption comes only from God Himself through Jesus Christ.